Diffusion in Ni-Based Single Crystal Superalloys with Density Functional Theory and Kinetic Monte Carlo Method (Communications in Computational Physics, 2018)
In the paper, we focus on atom diffusion behavior in Ni-based superalloys,which have important applications in the aero-industry. Specifically, the expressionsof the key physical parameter – transition rate (jump rate) in the diffusion can be givenfrom the diffusion theory in solids and the kinetic Monte Carlo (KMC) method, respectively.The transition rate controls the diffusion process and is directly related to theenergy of vacancy formation and the energy of migration of atom from density functionaltheory (DFT). Moreover, from the KMC calculations, the diffusion coefficientsfor Ni and Al atoms in the γ phase (Ni matrix) and the $γ^′$ phase (intermetallic compoundNi3Al) of the superalloy have been obtained. We propose a strategy of timestepping to deal with the multi-time scale issues. In addition, the influence of temperatureand Al concentration on diffusion in dilute alloys is also reported.